THE EFFECT OF PRODUCT ATTRIBUTES ON REPURCHASE INTENTION THROUGH UTILITARIAN VALUE IN READY TO DRINK COFFEE BEVERAGES IN SURABAYA - Monica Adjeng Erwita (Inovbiz: Jurnal Inovasi Bisnis, 2023)
This study aims to determine the effect of content sensory attribute beliefs, packaging and branding attribute beliefs, content functional attribute beliefs on utilitarian value through repurchase intention on RTD coffee products in Surabaya.The sampling technique used nonprobability sampling with the quota sampling method. The sample taken was 130 respondents who were consumers of RTD products. While the tool used to retrieve and collect data is an online questionnaire via google form. The data analysis technique uses a Structural Equation Model (SEM) using SmartPLS 4.0 softwareThe results of this study indicate that the effect of ready to drink coffee product attributes on repurchase intention through utilitarian value has a significant positive effect.